KETERKAIATAN PUSAT PERTUMBUHAN TERHADAP WILAYAH HINTERLAND (BERBASIS MODEL GRAVITASI) - Achmad Chumaini; Sofyan Syahnur (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstrack                                                                The purpose of this study the economic linkage of the districts/ cities in the province of Aceh towards the hinterland area. In this study, The GRDP variables used is based on the constant price of 23 districts/cities in the province of Aceh and the distance from the growth center to the hinterland area.  Data of this study used is panel data in the 2012-2016. The data by conducting chow, housman and multiple langgrange extant trials, and from the results of the model test it can be concluded for the three growth center for Banda Aceh, Lhoksemawe and west Aceh. Banda Aceh based on the chow test and Hausman, Test choose the fixed effect model in Banda Aceh as the center of growth positive for the test area trial effect areas to the hinterland region but not significant results. While the Lhoksemawe city as the most appropriate growth center used a random effect model testing which is more accurately estimated that lhoksemawe which is the center of growth has a positive impact on its hinterland area and the results are significant. West Aceh region uses the common effect model testing  for estimation to show positive results but the results are not significant. This results of this study are expected to be an input for the government in improving infrastructure, especially road conditions. Keywords: GRDP, Distance between municipal districts